Vinylcyclopropane [3+2] Cycloaddition with Acetylenic Sulfones Based on Visible Light Photocatalysis. Issue 18 (4th March 2022) - Luque, Adriana; Groß, Jonathan; Zähringer, Till J. B.; Kerzig, Christoph; Opatz, Till
Abstract: The first intermolecular visible light [3+2] cycloaddition reaction performed on a meta photocycloadduct employing acetylenic sulfones is described. The developed methodology exploits the advantages of combining UV and visible‐light in a two‐step sequence that provides a photogenerated cyclopropane which, through a strain‐release process, generates a new cyclopentane ring while significantly increasing the molecular complexity. Mechanistic studies and DFT calculations indicate an energy transfer pathway for the visible light‐driven reaction step. This strategy could be extended to simpler vinylcyclopropanes. Abstract : A new visible light‐mediated intermolecular [3+2] cycloaddition reaction of meta photocycloadducts with acetylenic sulfones catalyzed by iridium complexes has been developed. The strain energy contained in the photogenerated vinylcyclopropane system enables efficient access to a new complex molecular scaffold under very mild conditions. DFT‐calculations and time‐resolved optical spectroscopy studies substantiated a triplet energy transfer mechanism.